Experiences of medical traumatic stress in parents of children with medical complexity. (29th August 2022) - Dewan, Tammie; Birnie, Katie; Drury, Julie; Jordan, Isabel; Miller, Megan; Neville, Alexandra; Noel, Melanie; Randhawa, Alam; Zadunayski, Anna; Zwicker, Jennifer
Abstract: Background and Objectives: Parents of children with medical complexity (CMC) experience high levels of stress and adverse mental health outcomes. Pediatric medical traumatic stress (PMTS) could be an important contributor that has not yet been explored. PMTS describes parents' reactions to their child's illness and medical treatment and can lead to post‐traumatic stress symptoms. This is the first study to describe the experiences and impact of PMTS among parents of CMC. Methods: We conducted semi‐structured interviews with 22 parents of CMC. Reflexive thematic analysis was used to generate themes that described the experiences of PMTS and potential contributing factors in the healthcare setting. Themes were validated by study participants. Results: Parents experienced a spectrum of events and circumstances that impacted PMTS. These corresponded to three major themes: (a) the distinctive context of being the parent of a CMC, (b) interactions with healthcare providers that can hurt or heal and (c) system factors that set the stage for trauma. The consequences of repeated PMTS were a common point of emphasis among all the themes. Parents identified numerous changes that could mitigate PMTS such as acknowledgement of trauma and provision of proactive mental health support. Conclusions: Our study highlights the issue of PMTS among parents of CMC and presents opportunities to mitigate their traumatic experiences. Supporting the integration of trauma‐informed care practices, increasing awareness of PMTS and advocating for parental mental health services could better support parents and families.